Bloody Nipple Discharge in an Adolescent Girl: Unusual Presentation of Juvenile Fibroadenoma - Hsien Liu; Ming-Lun Yeh; Kai-Jen Lin; Chih-Kun Huang; Chao-Ming Hung; Yaw-Sen Chen (Pediatrics and Neonatology, 2010)
Fibroadenoma accounts for 50–60% of all breast mass lesions in adolescents. It usually presents as a unilateral palpable breast mass. In contrast, bloody nipple discharge rarely occurs in childhood. We report the case of a 12-year-old pubertal girl who presented with a solitary breast mass and bloody nipple discharge. Physical examination and ultrasound showed a right breast subareolar homogenous mass, about 2.5 cm in diameter, near the lactiferous duct. Histologic diagnosis of the mass revealed a juvenile fibroadenoma with infarction and hemorrhage. The unusual clinical presentation and possible etiology in this patient is described, and the proper management of bloody nipple discharge in pediatric patients is discussed in association with a literature review.